The Sensor Occlusion SEN0257 on the Infusion Device Analyzer 2 Channel with TFT Display ensures high accuracy in detecting occlusions. - Ach Jiddan Asrori'; Endro Yulianto; Triana Rahmawati (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Syringepump and Infuspump function to provide drugs or fluids that are carried out directly and continuously for a certain period of time through a blood vessel. Often encountered problems of blockage or occlusion in the use of infusion pumps and syringe pumps. Occlusion in the infusion device causes the incoming drug fluid to not flow constantly. Occlusion limit set at 20 Psi according to ECRI. To ensure this, proper calibration is required at least once a year. The purpose of this research is to analyze the accuracy of the pressure sensor on the Occlusion measurement on the Infusion Device Analyzer 2 Channel showing TFT. This study has 2 channels so that it can calibrate 2 tools simultaneously. The design of this module uses a Water Pressure Sensor to measure occlusion and a solenoid valve for pressure simulation. When the sensor is depressed, the sensor detects the pressure and is processed by the Arduino. The pressure results are then displayed on a 7-inch TFT LCD in the form of graphs and numbers in real time and stored on the SD card.